Nanoscale scanning electron microscopy based graphitization in tetrahedral amorphous carbon thin films. (October 2016) - Klein, F.; Treske, U.; Koitzsch, A.; Cavicchia, D.R.; Thönnißen, C.; Frömter, R.; Roch, T.; Mühl, T.
Abstract: Electron beam lithography is a powerful maskless tool to fabricate structures on the nanometer scale. Here, we show that low-keV-electron beams enable a direct patterning of tetrahedral amorphous carbon (ta-C) thin films by inducing a local graphitization without the need for any resist or development process step. Irradiation with 4 keV electrons leads to a local decrease of the ta-C film's electrical resistance and an increase of both the sp 2 /sp 3 -ratio and the material's work function. We investigate the impact of electron exposure on ta-C by a variety of microscopy as well as spectroscopy methods including scanning tunneling microscope-based current-distance spectroscopy, conductive atomic force microscopy, spatially resolved ultraviolet and x-ray photo emission spectroscopy, and μ -Raman spectroscopy. The electron exposure has been performed under ultrahigh vacuum conditions to prevent from electron-induced deposition of contaminants which may obstruct the application of surface-sensitive analysis techniques to the modified ta-C films.